DESAKRALISASI DAN ALENASI MANUSIA DALAM PERADABAN MODERN PERSPEKTIF TRADISIONALISME SEYYED HOSEIN NASR - Mohammad Subhi (Universitas Paramadina, 2014)
AbstractModern Civilization erased the Sacred from western philosophicalhistory through desacralization process. For Seyyed Hossein Nasr, result ofthe process is human alienation. This article aim to explain Seyyed HosseinNasr’s criticism on modern civilization.